Kant and “tabula Russia” - Chaly, Vadim (Con-Textos Kantianos. International Journal of Philosophy, 2023)
The article offers an attempt to understand the present state of Kant’s legacy in Russia on the threshold of the Tercentenary. An explanans is found in the metaphors of “tabula rasa” and “unplowed virgin soil,” first used by Leibniz in relation to Russia in his letters and memoranda addressed to tsar Peter I and other members of the Russian elite, which became the country’s “absolute metaphors to live by” up to present time. Several known and unknown episodes from the history of the reception of Kantian ideas, his followers in Russia, and the transformation of the urban environment of Kant’s life in Königsberg, as it was becoming Kaliningrad, are presented through the prism of this metaphor. Without hoping to make specific recommendations of any use from such metaphorical grounds, this study aims to emphasize the depth, interconnectedness, and basic, metaphysical tension of the relationship between Europe and Russia, which cannot be terminated at will by either side, or by a third party. In a situation where the sides are doomed to dialog, Kant, appropriated by Russia as its “subject,” occupies the unique position of mediator of philosophical understanding and peaceful action.